DETERMINAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DI INDONESIA - Husaini Husaini; Meily Trinesia (Jurnal Akuntansi, 2020)
This study is aimed to prove the influence of corporate characteristics on corporate social responsibility disclosure. The sample in this study is a non-financial company listed at the Indonesia Stock Exchange in 2013-2017. Methods of data collection used purposive sampling techniques and consisted of 250 companies. The results showed that size and government ownership of the company has a positive effect on corporate social responsibility, while the age of the company, foreign ownership, leverage, profitability, industry type, and auditor type has no effect on corporate social responsibility disclosure.